The effect of 0.03% flurbiprofen and 0.1% indomethacin eye drops and oral indomethacin on the pupil diameter in the extracapsular cataract surgery - Mu'tasimbillah Ghozi Mu'tasimbillah Ghozi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Intraocular surgery releases prostaglandin. Prostaglandin caused miosis and inflammatory reaction. Flurbiprofen and Indomethacin are antiprostaglandin agents.Objectives: This study was aimed to compare the effects of flurbiprofen and indomethacin eye drop and flurbiprofen tablet orally in preventing surgically induced miosis to dilated pupils during extracapsular cataract surgery.Methods: Measurement of the diameter of dilated pupil before and during extracapsular cataract surgery. Analysis variance and Tukey Studentized Rest Test were used to analyse the result.Results: No statitical significant difference was found in pupil diameter among the three groups except the stage of capsulotomy and inspiration-aspiration among those who received flurbiprofen and indomethacin eye drops.Conclusion: Flurbiprofen 0.03% eye drop was significantly stronger than Indomethacine eye drop 0.1% in preventing surgically induced miosis at extracapsular cataract surgery especially in both stage of capsulotomy and inspiration-aspiration and type manipulation.Keywords: cataract surgery - anterior capsulotomy - lens extraction - insiparition-aspiration - miosis -antiprostaglandin